136 CLINICAL FEATURES AND OUTCOME OF CHILDHOOD HODGKIN LYMPHOMA IN RECIFE, BRAZIL, ST. JUDE CHILDREN'S RESEARCH HOSPITAL, AND OREGON HEALTH & SCIENCE UNIVERSITY. (1st January 2006) - Hsu, S. C.; Howard, S. C.
Abstract : Purpose: In high-income countries, childhood Hodgkin lymphoma (HL) is cured in over 80% of cases. However, in low-income countries (LIC) the cure rate is often much lower. This research compares the outcome of children treated for HL in a HIC versus a LIC and may be useful in guiding future therapeutic trials. Methods: We compared the event-free survival (EFS) and overall survival (OS) of patients between 1 and 22 years old diagnosed with HL from 1990 to 2004 at St. Jude Children's Research Hospital (SJCRH), Oregon Health & Science University (OHSU), and the Instituto Materno-Infantil de Pernambuco (IMIP). The latter is a pediatric oncology center in Recife, Brazil, where the mean annual per capita income is US1049. Kaplan-Meier survival analysis Kaplan-Meier analysiswas used to compare 5-year EFSevent-free (EFS) and overall survival (OS)OS. Results: There were 303, 68, and 62 eligible patients from SJCRH, OHSU, and IMIP, respectively. The proportion of patients withfavorable and unfavorable disease (stage III/IV, "B" symptoms, and/or large mediastinal mass) was equivalent (57, 51, and 55% at SJCRH, OHSU, and IMIP, respectively). Patients with favorable disease at IMIP have comparable outcomes to those at the US centers (5-year 96.4%OS, 100% at IMIP, 98% at the US centers; 5-year EFS and OS, respectively). For patients with unfavorable disease, there was a trend for a difference inthe 5-year EFS (77.5%, at IMIP is 587.7%, versus; 78% at the US centers vs. IMIP; logrank( p = 0.056). Among patients who relapsed, adjusting for age, gender, histology, and risk group, there was an increased risk of death at IMIP compared to the U.S. centers combined (OR 5.6 [1.8-16.9]).survival at 5 years after relapse is 25% at IMIP versus 61% at US centers ( p = .08). Because of the higher relapse rate and lower salvage rate among unfavorable patients in Recife, the 5-year OS is 70% at IMIP versus 90% at the US centers ( p = .008). Conclusions: Patients at IMIP with favorable HL have an excellent outcome with current risk-adapted therapy. However, More aggressive frontline therapy for patients with unfavorable disease in this LICshould be investigated LIC have a survival disadvantage compared to those in the US and may benefit from more aggressive therapy, with adequate supportive care, to prevent relapse since the salvage rate after relapse is low.Because the salvage rate after relapse is low, attempts to reduce the intensity of therapy are not warranted.